2020
DOI: 10.7202/1069582ar
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Literature on the Benefits and Drawbacks of Participatory Action Research

Abstract: This paper reviews Participatory Action Research as a methodology. It maps the origins of Participatory Action Research (PAR) and discusses the benefits and challenges that have been identified by other researchers in utilizing PAR approaches in conducting research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 11 publications
0
26
0
3
Order By: Relevance
“…Advantages of action research in this context included: high level findings of direct practical relevance and application of the project to academics and practice education staff; the interrogation of real time qualitative data by all members of the group developing research capabilities of those involved; and increased understanding of programme issues and impact of IPL activities within education and practice arenas (Waterman and Hope 2008). The complexity of action research was challenging, particularly experiencing delays working within a group involving stakeholders and organisations as membership fluctuated (Bennet 2004). Each study member had to become reflective and analytical about their own practice in the development, delivery and evaluation of the study programme and the impact on practice.…”
Section: Ipl Programmementioning
confidence: 99%
“…Advantages of action research in this context included: high level findings of direct practical relevance and application of the project to academics and practice education staff; the interrogation of real time qualitative data by all members of the group developing research capabilities of those involved; and increased understanding of programme issues and impact of IPL activities within education and practice arenas (Waterman and Hope 2008). The complexity of action research was challenging, particularly experiencing delays working within a group involving stakeholders and organisations as membership fluctuated (Bennet 2004). Each study member had to become reflective and analytical about their own practice in the development, delivery and evaluation of the study programme and the impact on practice.…”
Section: Ipl Programmementioning
confidence: 99%
“…Reimer [23] highlights the 'inherent relationship researchers have with local individuals hired to assist in the research process' as a disadvantage. Adding to Reimer, Bennett [3] argues 'not everyone within the community will want to partake in participatory research'. To avoid these challenges, it is important as a researcher to identify the limitations of the research at the beginning and establish trust with the community.…”
Section: Participatory Methodsmentioning
confidence: 99%
“…One promising approach to address these criticisms is Participatory Action Research (PAR). The PAR approach is highly conducive to enable marginalized people (in this case people with lived experience of mental illness) to be meaningfully involved in areas of concern to them through developing their capacities and address more holistically the complex factors that hinder their involvement [30][31][32]. Our recent systematic review (Abayneh et al, in progress) found that PAR is a well-established approach to involve service-users within mental health systems in highincome countries; however, there are few similar studies from LMICs.…”
Section: Introductionmentioning
confidence: 99%